Digital education in the social investment model of Gross Domestic Product growth in the context of Industry 4.0 - Yankovskaya, Veronika V.; Suglobov, Aleksandr E.; Bykovskaya, Natalya V.; Mustafin, Timur A. (Frontiers in Education, 2023)
The motivation for this research was the desire to disclose the potential for human potential development that is created by Industry 4.0. The goal of this paper is to study the modern international experience and prospects for implementing the social investment model of economic growth under the conditions of Industry 4.0 with the help of the development of digital education. The method of regression analysis is used to model the econometric dependence of human development on digital education in 2019-2021. The paper’s contribution to the literature consists in the development of scientific provisions of the concept of the social investment model of economic growth through reconsidering the approach to human potential development with the help of education under the conditions of Industry 4.0. unlike the existing approach, which implies the foundation on traditional (pre-digital) education, this paper offers a new approach to human potential development under the conditions of Industry 4.0, which is based on digital education. The advantage of the authors’ approach is its allowing for the fullest use of new opportunities that open under the conditions of Industry 4.0. The main conclusion of this research is that under the conditions of Industry 4.0, the social investment model of economic growth should be based on digital education.